2019
DOI: 10.3390/ijerph16234794
|View full text |Cite
|
Sign up to set email alerts
|

Weekly Dose-Dense Paclitaxel and Triweekly Low-Dose Cisplatin: A Well-Tolerated and Effective Chemotherapeutic Regimen for First-Line Treatment of Advanced Ovarian, Fallopian Tube, and Primary Peritoneal Cancer

Abstract: A combination of cytoreductive surgery, either primary (PCS) or interval (ICS), and chemotherapy with a platinum-paclitaxel regimen is the well-accepted treatment for advanced-stage epithelial ovarian cancer (EOC), fallopian tube cancer (FTC), and primary peritoneal serous carcinoma (PPSC), but it is still uncertain whether a combination of dose-dense weekly paclitaxel and low-dose triweekly cisplatin is useful in the management of these patients. Therefore, we retrospectively evaluated the outcomes of women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…The evaluation of image finding was based on Response Evaluation Criteria in Solid Tumors (RECIST), version 1.1 [127][128][129]. Criteria of progression or recurrence were based on findings of clinical symptoms or signs accompanied with image findings and tumor markers described elsewhere [41,130,131].…”
Section: Assessmentsmentioning
confidence: 99%
“…The evaluation of image finding was based on Response Evaluation Criteria in Solid Tumors (RECIST), version 1.1 [127][128][129]. Criteria of progression or recurrence were based on findings of clinical symptoms or signs accompanied with image findings and tumor markers described elsewhere [41,130,131].…”
Section: Assessmentsmentioning
confidence: 99%
“…13 Previous studies have reported that platinum combined with other chemotherapeutic drugs, such as paclitaxel, for epithelial ovarian malignancies has become a general choice for postoperative fallopian tube cancer. 14,15 In this case, the endometrial adenocarcinoma was a lowgrade malignant tumor (grade I), which is mainly treated with surgery and postoperative chemoradiotherapy combined with hormone therapy, whereas the primary serous fallopian tube carcinoma is highly malignant, and is treated by surgery combined with chemotherapy. According to the treatment principle of multiple primary tumors, paclitaxel combined with platinum regimen was administered.…”
Section: Discussionmentioning
confidence: 96%
“…Overall, randomized trials have suggested equivalent or improved efficacy with dose-dense regimens relative to conventionally dosed therapy, though toxicities are usually higher with the dose-dense regimens [ 25 , 26 , 27 , 28 , 29 , 30 ]. In some cases, dose-dense chemotherapy has been shown to be well tolerated and could be considered as frontline treatment in advanced ovarian cancer [ 31 , 32 ]. In patients with optimally resected stage III EOC, GOG 158 demonstrated that carboplatin with paclitaxel is less toxic, easier to administer, and not inferior to cisplatin plus paclitaxel [ 33 ].…”
Section: Role In Front-line Treatmentmentioning
confidence: 99%